A Modified NMOS Inverter With Rail-To-Rail Output Swing and Its Application in the Gate Driver Integrated by Metal Oxide TFTs - Pei-An Zou; Jun-Wei Chen; Kai Xiang; Lei Zhou; Jian-Hua Zou; Miao Xu; Lei Wang; Wei-Jing Wu; Jun-Biao Peng; Mansun Chan (IEEE Journal of the Electron Devices Society, 2021)
A modified NMOS inverter employing output feedback theme has been proposed in this paper. The feedback structure can guarantee high voltage output at a wider range of low voltage input. The proposed inverter and the conventional pseudo-CMOS inverter are both fabricated by top gate coplanar In-Zn-O thin film transistors (IZO TFTs) for comparing. The experimental results show that the proposed inverter possesses better static performance exhibiting noise margin NML/NMH, output swing VOL-VOH, switching threshold VM of 3.95/5.82 V, 0.05-9.97 V, 4.05 V, respectively. In addition, the proposed inverter is also applied in the gate driver integrated by IZO TFTs to further verify its function. Benefited from good static characteristic of the proposed inverter, the output module is well controlled to produce a good output waveform. It is measured that the output waveform of the 120th-stage has almost no distortion compared with that of the 1st-stage at 25 kHz.